Analytical investigation of collector optimum tilt angle at low latitude - Aja, O.C. (2013)
An analytical investigation on the optimum tilt angle for solar collectors at low latitude, a case study of Universiti Teknologi PETRONAS (UTP), 4.39°N and 100.98°E, Malaysia is presented in this work. The study employed Hay, Davies, Klucher, and Reindl (HDKR) anisotropic sky model to evaluate the available hourly solar radiation on inclined surface using the location metrological data. The tilt angles considered were 0° to 30° in step of 3° with the inclusion of the location latitude angle. The study employed the ratio of global solar radiation on tilted surface to the global solar radiation on horizontal surface in the decision of the optimum tilt. The system equations were converted to MATLAB codes to solve for the optimum tilt angles. The results show that the optimum tilt varies monthly but gave zero degree for south facing collector for the months of April to August; thus, the investigation also considered north facing orientation for the months of April to September. The optimum annual tilt angle for the location using the tilt to horizontal radiation ratio was found to be equal to the location latitude angle. Using the conventional average of the monthly optimum tilt angles, the annual optimum tilt angle was found to be 9.75° for south facing collector. Considering seasonal optimum tilt angle for the location using the tilt to horizontal radiation ratio, 18° facing south was found to be the optimum tilt angle for rainy season (September to March) and 15° facing north for dry season (April to August). Employing the average of monthly optimum tilt method, the seasonal optimum tilt angle was found to be 17° for rainy season and 12° facing north dry season. The effect of dust on the collector was considered with reference to literature and the annual tilt angle of 15° facing south was recommended for the location in the case of large solar collector that cannot be monthly or seasonally adjusted. © 2013 AIP Publishing LLC.